Exploring the theory of resilient commitment in emerging adulthood: a qualitative inquiry - Sibley, D. Scott (Kansas State University, 2015)
The purpose of this qualitative study was to explore how emerging adults (18-29 year olds) define commitment in romantic relationships and have created meaning from the positive and negative examples of commitment they have witnessed. Twenty (10 men, 10 women) unmarried emerging adults were interviewed individually. Through the use of grounded theory four themes emerged to explain how emerging adults have constructed their understanding of commitment: complete loyalty, investment in the relationship, continual communication, and parental influence. From observing negative and positive examples of commitment, emerging adults learned to discern healthy and unhealthy characteristics of romantic relationships, are working to be different, and have learned what to do to make a committed relationship work long term including the sub-themes of unitedly persevere, prioritize the relationship, consider your partner, give substantial effort, have fidelity. These results extend our knowledge about the model of resilient commitment, and the critical purpose of meaning making. Implications for intervening with emerging adults to strengthen future romantic relationship stability are discussed.
Keywords: Commitment; Emerging adulthood; Resilience; Romantic relationships; Decision-making; Family of origin; Individual & Family Studies (0628)